Assessment of export-embodied CO2 emissions from China’s ocean industries: implications for formulating sustainable ocean policies - Zheng, Li; Zhang, Zenkai; Yao, Ye; Duan, Xiaofeng; Li, Mingxin; Zeng, Zhao; Du, Huibin (Frontiers in Marine Science, 2024)
The ocean industries are characterized by being export-driven. The exports of ocean industries (hereafter termed ocean exports) caused environmental pollution with amounts of CO2 emissions and thereby affected climate change. There is a need, therefore, for accurate assessments of CO2 emissions embodied in ocean exports—which can help policymakers adopt targeted emission-reduction measures to formulate sustainable ocean policies. However, few studies of ocean-industry emissions considered impacts in sectoral and trade pattern heterogeneity, especially from export perspective. To fill this gap, we measured and evaluated the export-embodied CO2 emissions from China’s ocean industries, based on our newly developed high-resolution and comparable time-series environmentally extended input–output database, called EE-DPN-OEIOT. The results showed that China’s ocean exports generated 94.3 Mt of embodied CO2 emissions in 2017, with nearly 40% originating from processing ocean exports. Regarding the evolution from 2007 to 2017, the total export-embodied CO2 emissions from ocean industries decreased by 7.3%, while the embodied CO2 emissions in processing ocean exports increased by 50.1%. From 2007 to 2017, the decrease in carbon emission intensity was the major driving factor of the downturn in export-embodied CO2 emissions across the total ocean economy and for seven ocean subsectors (60%), while the export-scale effect primarily drove the increases in CO2 emissions. Moreover, there were disparities in the driving factors behind changes in embodied CO2 emissions between processing and non-processing ocean exports. Based on our findings, we proposed three recommendations from a trade perspective to facilitate low-carbon sustainable transition of China’s ocean economy, thus better fulfilling Sustainable Development Goal 14.